Enhanced antibacterial and genoprotective properties of nanoliposomal Satureja hortensis L. essential oil - Cagal, Munevver Muge; Taner, Gokce; Kalayci, Sadik; Duman, Gulengul (Taylor & Francis Ltd, 2025)
Nanoliposomes are drug delivery systems that improve bioavailability by encapsulating therapeutic agents. The main objective of this study was to investigate the effects of nanoliposomal (NL) formulation on enhancing the bioavailability of essential oil. The essential oil of Satureja hortensis (SHO) was encapsulated in nanoliposomes (SHNLs). Physicochemical characterizations of NL formulations (size, charge, polydispersity index [PDI]) were evaluated by dynamic light scattering technique. The nanoliposome encapsulation efficiency (EE) was calculated as 89.90%. The prepared bionanosystems demonstrated significant antibacterial activities against Escherichia coli ATCC 10536, Pseudomonas aeruginosa ATCC 15442, and Staphylococcus aureus ATCC as determined by the agar diffusion method and microdilution tests. Minimum inhibitory concentration (MIC) values for SHNLs were found to be 5.187 mu g/mu L for E. coli and 2.59 mu g/mu L for both P. aeruginosa and S. aureus. Importantly, despite the lower substance content, both SHNLs and SHO exhibited comparable antibacterial activity against all tested strains. Furthermore, in order to determine the toxicity profile and possible effects on DNA damage or repair both the genotoxic and antigenotoxic effects of SHNLs were assessed using the cytokinesis-blocked micronucleus (CBMN) method in human lymphocyte cultures. The experimental data collectively indicate that the NL formulation of the S. hortensis essential oil enhances antibacterial activities and provides genoprotective effects against DNA damage. This highlights the significance of liposomal formulations of antioxidants in augmenting their biological activity. The results indicate that SHNLs can be a safe antibacterial agent for the pharmaceutical industry.
Keywords: Nanoliposomal formulation; Satureja hortensis; genotoxicity; micronucleus assay; summer savory